ANALISIS STRATEGI BERSAING PT CEQUAL INDONESIA DALAM MENCIPTAKAN COMPETITIVE ADVANTAGE DI INDUSTRI CONTENT PROVIDER - , Laurensius Riasko Pratiknyo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This paper planned to examine internal and external factors that affect the ability of PT Cequal Indonesia for creating competitive advantage in the content provider industry in Indonesia. Analysis of competitive strategy is done by evaluating the strategies that have been implemented by PT Cequal Indonesia and formulated new strategies which one can be applied by PT Cequal Indonesia for compete in the future. From the analysis of external environment, it is known that the industry is heavily influenced by the stakeholders from external companies, such as consumers, government and telecommunication operators. While the results of internal environmental analysis is obtained that the organizational structure and financial factors become a major weaknesses for PT Cequal Indonesia. Human resources factors derived from programmers with high competence become a major source of strength for the company. The conclusion that can be obtained from the results of this analysis is a strategy for continuing differentiation by PT Cequal Indonesia has right to implemented. In this case managements still needed to think of various alternative strategies in order to support PT Cequal Indonesia may still exist in the content provider industry.